Evaluation of nutrient composition and bone-promoting activity of miiuy croaker (Miichthys miiuy) bone - Ouyang, Qianqian; Liu, Lifen; Liu, Lili; Li, Yi; Qi, Yi; Wu, Kefeng; Zhu, Guoping; Ye, Hua (Frontiers in Nutrition, 2024)
IntroductionThe objective of this study was to improve the economic value of the processed by-products of farmed miiuy croaker (Miichthys miiuy) by evaluating the nutrient composition and osteogenic activity of its bones. We prepared Miichthys miiuy bone peptides (MMBP) and analyzed their osteogenic potential.MethodsWe assessed the osteogenic activity of MMBP by molecular docking, MC3T3-E1 cell proliferation assay and zebrafish growth model, and evaluated its effect on osteoporosis (OP) using a retinoic acid-induced osteoporosis rat model.ResultsSciaena ossificans bone is rich in nutrients, including 11.40% water, 59.30% ash, 1.60% crude fat, 27.10% crude protein, and 0.58% total sugars. The total amino acids account for 22.13%, including 4.33% essential amino acids and 17.80% non-essential amino acids. The mineral content was rich, with calcium, phosphorus and selenium contents of 162511, 7151, and 0.264 mg/kg, respectively. MMBP significantly promoted the proliferation of MC3T3-E1 cells, facilitated the growth and bone development of zebrafish. In retinoic acid-induced osteoporosis rat model, increased the serum calcium and phosphorus levels, attenuated the calcium loss, and reduced the tartrate-resistant acid phosphatase and alkaline phosphatase (ALP) activities and significantly improved bone density. MMBP shows potential as a functional food ingredient due to its osteogenic properties, which may help promote bone growth and maintain bone health. These findings provide a scientific basis for the high-value utilization of Miichthys miiuy by-products and a new direction for the development of novel functional food ingredients.